(untitled) (Medico Legal Update, 2020)
Cross sectional study was carried out to evaluate the level of hepcidin in sera of pregnant women with anemia. The study include 86 sample from women with reproductive age(18-35)year. Forty six sample collected from pregnant women with anemia and forty sample from healthy pregnant women as control group in 2nd and 3rd trimester, all samples were collected from Healthy center and Specialized Clinics in Samarra for the period from 14 December 2018 to 22 January 2019. The study include the determination of Packed cell volume (P.C.V) ratiohemoglobin-Hb conc., Total Iron, total iron binding capacity-TIBC conc., Transferrin conc., Hepcidin conc., Total protein –TP conc., Albumin conc, Globulin conc., The activity of liver enzymes (Alanine aminotransferase-ALT, aspartate aminotransferase–AST and Alkaline phosphatase-ALP), the results showed thatthe levels of PCV ratio, Hb, total iron and hepciden significant decreased p?0.05 in pregnant women with anemia as compared with control group, with significant p?0.05 increase in level of TIBC, Transferrin, and the activity of AST and ALP in pregnant women with anemia as compared with control group, with no significant change p?0.05 to the level of total protein, albumin, globulin and the activity of ALT in pregnant women with anemia as compared with control group.